1998
DOI: 10.1209/epl/i1998-00563-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bulk modulus and reduced transition pressure in γ-Fe 2 O 3 nanocrystals

Abstract: Synchrotron radiation X-ray diffraction studies of γ-Fe2O3 have been performed with emphasis on the pressure-induced phase transformation γ(maghemite) → α(hematite) and the equation of state of the nanophase material. For γ-Fe2O3 the bulk modulus has been found to increase from 203 GPa for the bulk material to 305 GPa for 9 nm size crystals. At the same time the transition pressure decreases from 35 to 27 GPa. The reduced transition pressure is explained in terms of nucleation and growth, the larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
120
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 19 publications
11
120
1
Order By: Relevance
“…Neodymium is substantially less compressible than other lanthanide cations and the larger bulk modulus of NdFeO 3 compared to GdFeO 3 demonstrates the influence of Nd 3+ . Also, the binary oxide Cr 2 O 3 has a bulk modulus of 240(8) GPa [41] whereas Fe 2 O 3 has a bulk modulus of 203 GPa [42]. The large value of the bulk modulus of NdCrO 3 compared to other simple perovskites indicates it is one of the least compressible simple perovskites yet determined.…”
Section: Resultsmentioning
confidence: 99%
“…Neodymium is substantially less compressible than other lanthanide cations and the larger bulk modulus of NdFeO 3 compared to GdFeO 3 demonstrates the influence of Nd 3+ . Also, the binary oxide Cr 2 O 3 has a bulk modulus of 240(8) GPa [41] whereas Fe 2 O 3 has a bulk modulus of 203 GPa [42]. The large value of the bulk modulus of NdCrO 3 compared to other simple perovskites indicates it is one of the least compressible simple perovskites yet determined.…”
Section: Resultsmentioning
confidence: 99%
“…Similar behavior of the resistivity of the B16 phase versus pressure was also detected in nanocrystal PbS. The data obtained from a pressure range of 4-14 GPa for bulk PbS and of [8][9][10][11][12][13][14][15][16][17][18] GPa for nanocrystal PbS were fitted by d(ln R)/dPϭC, where C is constant. It found CϭϪ0.64 GPa Ϫ1 for bulk PbS and CϭϪ0.34 GPa Ϫ1 for nanocrystal PbS, as is shown by the solid lines in Fig.…”
mentioning
confidence: 76%
“…8 compared with corresponding bulk materials. However, Jiang et al 9 reported that for nanometer-sized ␥-Fe 2 O 3 particles the phase transition pressure ͑from ␥-Fe 2 O 3 to ␣-Fe 2 O 3 ͒ is lower than that for bulk material. They suggested that the larger volume change upon transition in the nanocrystals is the main factor in this case.…”
mentioning
confidence: 99%
“…7 Qadri et al 8 have also reported that the effect of reduced particle size in PbS nanocrystals is to elevate the transition pressure while the compressibility increases with decreasing particle size. However, Jiang et al 9 reported that for nanometer-sized ␥-Fe 2 O 3 particles the phase transition pressure ͑from ␥-Fe 2 O 3 to ␣-Fe 2 O 3 ) is lower than for bulk material. A similar result was also reported in TiO 2 for the rutile-to-␣-PbO 2 transition.…”
mentioning
confidence: 99%